Management of septic complications related to traumatic gastric injury using minimal invasive surgical techniques: case report - Kuliešius, Žygimantas; Grigaliūnas, Aurelijus; Šydeikienė, Raminta; Brimas, Gintautas; Lunevičius, Raimundas (Lietuvos chirurgija, 2015)
Background Incidence of stomach perforation following blunt trauma ranges from 0.02 to 1.7 per cent. Isolated traumatic rupture of the stomach is relatively uncommon and is usually treated by emergency laparotomy and gastric repair. Our aim was to present an unusual case of traumatic gastric transmural injury and its septic complications managed using minimally invasive surgery techniques. Case report 62 years male patient was admitted with epigastric tenderness and signs of acute gastrointestinal bleeding. The patient sustained a blunt abdominal trauma two weeks ago and had a history of gastric ulcer. The UGI endoscopy showed ulceration covering all the lesser curvature of the stomach without signs of active bleeding. Transabdominal ultrasound scan showed a collection of fluid within lesser sac, haematoma of anterior abdominal wall and small volume of free fluid in the abdominal cavity. The urgent surgery was discussed with the patient, however, he categorically refused to undergo it. Ultrasound guided percutaneous drainage of anterior abdominal wall abscess using 12 Fr drain and an endoscopic drainage through posterior gastric wall using two 7 Fr pigtail drains for a lesser sac abscess were performed when a CT-scan of the abdomen confirmed them. The patient was discharged on 35th day of hospitalization. The drains from the stomach were removed endoscopically in two months time. Conclusion Localized septic complications of traumatic gastric rupture can be effectively managed using percutaneous and transgastric minimally invasive surgery techniques.